Tracing the gender wage gap: Income differences between male and female university graduates in Germany - David Reimer; Jette Schröder (Zeitschrift für ArbeitsmarktForschung - Journal for Labour Market Research, 2006)
The aim of this paper is to shed light on the causal mechanisms leading to the gender wage gap, drawing on neoclassical as well as sociological labor market theories. A unique dataset from the 2001/2002 Mannheim University Social Sciences Graduate Survey, which overcomes several limitations of standard population surveys when investigating the gender wage gap, is used for the empirical analysis. The sample is homogenous with respect to the measures normally used in income analyses - all of the respondents are university graduates, have a degree in the same field of study, and are observed at career entry. Furthermore, the dataset includes detailed measures of human capital, job search, and career attitudes, which are usually not included in standard population surveys. The results of a sequence of nested regression models show that none of these measures reduces the gender wage gap substantially: on the contrary, the introduction of variables capturing human capital even leads to a small increase in the gap. This indicates that the earnings differential between female and male graduates in the study would be even larger if women had the same human capital endowment as men. Considering that a wage gap of almost 7 percent remains even with the extensive set of variables in the analysis, there is some indication that female university graduates are facing wage discrimination on the German labor market.
Keywords: 330; Hochschulabsolventen; Lohnunterschied; geschlechtsspezifische Faktoren; Lohndiskriminierung; Bildungsertrag